2008
DOI: 10.1007/s10661-007-0118-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of dental unit waterlines in Istanbul, Turkey

Abstract: The water used in dental unit waterlines (DUWLs) acts as a coolant for the high-speed equipment and as an irrigant during dental treatments. There are kind of water tanks. DUWLs provide a favorable environment for microbial biofilm and multiplation primarily due to the high surface in the tubing and the character of fluid dynamics in narrow, smooth-walled waterlines. Biofilms can harbour opportunist pathogens such as Legionella sp., Pseudomonas sp. Several studies have shown that DUWLs have high levels of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
(21 reference statements)
4
23
0
Order By: Relevance
“…Most of tbe isolates are among the opportunistic pathogens that may pose health risks to immunocompromised individuals. For example, Göksay et al (2008) andVenkatesh et al (2006) found such bacteria to be an important source of crossinfection in hospitals. Some produce toxins which may cause mild inflammation to serious toxic shock (Venkatesh et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Most of tbe isolates are among the opportunistic pathogens that may pose health risks to immunocompromised individuals. For example, Göksay et al (2008) andVenkatesh et al (2006) found such bacteria to be an important source of crossinfection in hospitals. Some produce toxins which may cause mild inflammation to serious toxic shock (Venkatesh et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest levels of heterotrophic bacteria counts were found to be 200,200, 366,800 and 97,000 CFU ml −1 in air-water syringes, high-speed drills and the water source, respectively. Many studies have established the microbial contamination of dental units with reports of 10 3 -10 5 CFU ml −1 of bacteria detected in water samples from DUWLs (Göksay et al 2008;Miller 1996;Walker et al 2000;Williams et al 1995;Souza-Gugelmin et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…DUWLs support the formation of microbial biofilms since they are directly connected to municipal water, and also have stagnant water and average temperatures. It was reported as early as 1963 that DUWLs can be heavily contaminated with microorganisms (Blake 1963), and this has been confirmed more recently (Göksay et al 2008;Türetgen et al 2009). …”
Section: Introductionmentioning
confidence: 86%
“…A range of fungi, yeasts, protozoa and amoebae has also been identifi ed in DUWLs, although these organisms are far less prevalent and signifi cantly less abundant than bacteria (Kelstrup et al ., 1977 ;Porteous et al ., 2003 ;Singh and Coogan, 2005 ;Szyma ń ska, 2005 ;Göksay et al ., 2008 ). Protozoa and amoebae present in natural waters are frequently parasitised by intracellular Legionella bacteria, which are released upon death of the protozoa/amoebae they infect .…”
Section: Microorganisms Identifi Ed In Duwl Output Watermentioning
confidence: 99%